Differences of acute physiological responses between two high-intensity interval exercise modes in endurance and sprint type athletes - Cipryan, L.; Tschakert, G.; Hofmann, P. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
INTRODUCTION: A number of variables prescribe high-intensity interval exercise (HIIE) but the principle of individuality has to be respected also. Regarding HIIE, the effect of training mode has received limited scientific interest so far. Therefore, the aim was to compare the acute cardiorespiratory and metabolic response to short and long HIIE in endurance and sprint trained athletes. METHODS Sixteen highlytrained males (8 endurance (E) and 8 sprint (S) athletes, age 22.5±3.0 years, VO2max: E: 66.2±5.0 ml/kg/min; S: 56.8±5.0 ml/kg/min) volunteered in this study. The participants firstly performed a maximal incremental treadmill test. Then they performed a short (30s) and a long HIIE (180s), matched to one constant load exercise (CE) (50 % of vV O2max; total duration 32 min). Long and short intervals were identical for work/relief ratio (1:1) as well as for the relative work (vV O2max = 100 %) and relief intensity (passive). Ventilatory parameters, heart rate (HR) and lactate (La) were monitored during the exercise. A magnitude based inferences were employed within the statistical analysis (Batterham & Hopkins, 2005). RESULTS: The HR and V O2 peaks during the long HIIE clearly crossed the second ventilatory threshold (VT) while this peak cardiorespiratory response remained at the level of the first VT during the short HIIE. The differences between E and S athletes in mean HR response (bpm or % HRmax) were unclear in all trials. Endurance athletes performed the exercise interventions with moderately (CE) or largely (both HIIE modes) higher mean V O2. These differences were unclear or trivial when V O2 was expressed as a function of V O2max. Moderately lower RER values were found in endurance athletes. The E vs. S differences in mean La were unclear (both HIIE modes) or nearly perfect in CE, with higher values in sprint athletes. DISCUSSION: All exercise tests produced similar values in E and S athletes for mean HR and mean V O2 (% V O2max). However, E athletes performed the exercise trials with